Rendszerváltó évek. Széthullás időrendben - MSzMP 1988. december - 1989. Július . Years of Transition in Hungary. The Chronology of Downfall of the Hungarian Socialist Workers Party Between December 1988 and July 1989
Television program about the political and social issues of the transition period of Hungary.